462. IMPACT OF THE RATIO OF THE VISCERAL FAT AREA TO PSOAS MUSCLE AREA ON SURVIVAL FOR SURGICALLY RESECTED ESOPHAGEAL CANCER. (24th September 2022) - Sakai, Makoto; Sohda, Makoto; Uchida, Shintaro; Yamaguchi, Arisa; Watanabe, Takayoshi; Saito, Hideyuki; Nakazawa, Nobuhiro; Kuriyama, Kengo; Sano, Akihiko; Ogawa, Hiroomi; Yokobori, Takehiko; Shirabe, Ken; et al.
Abstract: Sarcopenia (the loss of skeletal muscle volume and/or quality) and obesity have received increasing attention in many malignancies because they are associated with postoperative complications and poor surgical outcomes. The synergic effects of muscle mass reduction with excess body adiposity in surgically resected esophageal cancer (EC) patients remains controversial, especially in non-obese patients. One hundred and six patients with EC who underwent surgery between 2006 and 2014 were included in this study. Reduction in muscle mass and excess body adiposity were defined as the ratio of the visceral fat area (VFA) to psoas muscle area (PMA) (V/P ratio) on the same axial computed tomography (CT) slice at the third lumbar vertebra (L3). A high V/P ratio was associated with higher age (p = 0.03), higher body mass index (BMI) (p<0.001), higher VFA (p<0.001), and increased age-adjusted Charlson comorbidity index (ACCI) (p = 0.005). Multivariate analysis revealed a high V/P ratio to be an independent prognostic factor for poor overall survival (OS) in EC patients who underwent surgery (p = 0.003). The prognostic value of the V/P ratio was still significant in EC patients with a BMI < 25. A high V/P ratio was associated with poor survival in surgically resected EC patients, even in non-obese patients. The V/P ratio as a surrogate marker of relative muscle mass reduction and fat accumulation may have prognostic value in EC patients regardless of body composition differences.